Pengaruh Model Pembelajaran Realistc Mathematics Education terhadap Literasi Matematika Siswa Kelas VII SMP Negeri 2 Wonorejo - Qismatun Najah, Nina; Supriyo Supriyo; Miftahul Khoiri (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2026)
This study aims to analyze the effect of implementing the Realistic Mathematics Education (RME) learning model on improving students' mathematical literacy, particularly in social arithmetic material at SMP Negeri 2 Wonorejo. The research used a quantitative method with a quasi-experimental design in the form of a non-equivalent control group design. The population consisted of seventh-grade students from three classes, samples selected through purposive sampling based on preliminary test results: class VII B as the control group and class VII C as the experimental group. Research instruments included a validated observation sheet on student activities and an essay-type mathematical literacy test. Data analysis was conducted using normality tests, homogeneity tests, independent t-tests, and effect size calculation. The results indicated that student activities in the RME learning model were categorized as excellent. Hypothesis testing with an independent t-test yielded tcalculated = 2.81 > ttable = 1.56. The average post-test score of the experimental group (73.00) was higher than that of the control group (50.41). The effect size calculation resulted in d = 1.75, which falls into the large effect category. Thus, it can be concluded that the RME learning model has a positive and significant influence on improving students' mathematical literacy.